Fatores explicativos do nível de evidenciação voluntária de informações sobre recursos intangíveis das empresas listadas na BM&FBOVESPA - Fontana, Fernando Batista (Universidade do Vale do Rio dos Sinos, 2011)
The objective of this study was to investigate the explicative factors of the level of voluntary disclosure of information about intangible resources in companies listed on BM&FBovespa. Considering market inefficiency, the existence of information asymmetry between managers and shareholders/investors, the Agency Theory indicates that the disclosure might result in the reduction of agency costs. On the other hand, the Proprietary Costs Theory establishes that the disclosure of information would generate cost to the company. The justification to the study is grounded on the fact that even with the large number of studies found about disclosure of information, in an international scope, the number of studies on the level of disclosure of information about intangible resources is still scarce, and in national scope no studies were found. The choice of information about intangible resources was configured by the recognition that they differentiate the competitive potential of a business organization and disclosure of that kind of information could affect the company value. This is an explanatory study, with a qualitative and quantitative approach of the evidences. The sample included 29 companies. The document analyzed was their annual report. The annual reports were downloaded from the websites of the companies, and are related to the period that goes from 2005 to 2009. The level of disclosure of information about intangible resources was measured through the content analysis of annual reports, using indicators and, subsequently, by indexes, according to the Macagnan model (2005). The analysis technique used was multiple linear regression with panel data. The main findings show that the following hypotheses are not rejected: size, leverage, liquidity, market to book ratio and time of registration in the CVM, at a significance level of 1%, as explanatory factors of the level of disclosure of information about intangible resources in general. The hypotheses: profitability, growth, free float, dividends per share, stock volatility and efficiency were rejected as explanatory factors for the level of disclosure of information about intangible resources in general. As a differential contribution of this study the identification and not rejection of the hypothesis time of registration in CVM stands out as one of the explanatory factors.
Keywords: Intangible resources; Voluntary disclosure; Information asymmetry; Recursos intangíveis; Evidenciação voluntária; Assimetria informacional; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis